2020
DOI: 10.1167/jov.20.10.13
|View full text |Cite
|
Sign up to set email alerts
|

Stronger saccadic suppression of displacement and blanking effect in children

Abstract: Humans do not notice small displacements to objects that occur during saccades, termed saccadic suppression of displacement (SSD), and this effect is reduced when a blank is introduced between the pre-and postsaccadic stimulus (Bridgeman, Hendry, & Stark, 1975; Deubel, Schneider, & Bridgeman, 1996). While these effects have been studied extensively in adults, it is unclear how these phenomena are characterized in children. A potentially related mechanism, saccadic suppression of contrast sensitivity-a prerequi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 117 publications
(188 reference statements)
1
6
0
Order By: Relevance
“…Such accounts fail to offer a potential explanation for our shape-change direction bias, and a row of other findings on transsaccadic change perception. For example, the improvement of displacement detection due to accompanying object-form changes ( Demeyer et al, 2010 ) or other accompanying feature changes ( Tas et al, 2012 ), or a stronger blanking effect for children compared to adults ( Stewart, Hübner, & Schütz, 2020 ). Overall, an account based on evidence evaluation for or against a stable transsaccadic percept appears to be the more comprehensive theory for visual stability across saccades and, with consideration of feature-specific transsaccadic expectations, the most likely theory behind our findings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Such accounts fail to offer a potential explanation for our shape-change direction bias, and a row of other findings on transsaccadic change perception. For example, the improvement of displacement detection due to accompanying object-form changes ( Demeyer et al, 2010 ) or other accompanying feature changes ( Tas et al, 2012 ), or a stronger blanking effect for children compared to adults ( Stewart, Hübner, & Schütz, 2020 ). Overall, an account based on evidence evaluation for or against a stable transsaccadic percept appears to be the more comprehensive theory for visual stability across saccades and, with consideration of feature-specific transsaccadic expectations, the most likely theory behind our findings.…”
Section: Discussionmentioning
confidence: 99%
“…An accumulation of agreements with transsaccadic expectations for every feature may outweigh contradictions with transsaccadic expectations on spatial position such as large displacements or even blanks. This may become apparent in intrasaccadic displacement studies that found higher detection thresholds for naturalistic stimuli ( McConkie & Currie, 1996 ); or a smaller blanking effect with complex stimuli ( Tas et al, 2012 ; Stewart, Hübner, & Schütz, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is consistent with the interpretation of a greater reliance on the saccade landing site to localize the post-saccadic target. There is at least some evidence showing that children make less precise saccades than adults do, and therefore may have stronger expectations of greater intrinsic noise in the visuomotor system than adults ( Stewart et al, 2020 ). However, more studies directly manipulating spatial uncertainty using experiments and/or computational modeling (e.g., Atsma, Maij, Koppen, Irwin, & Medendorp, 2016 ; Niemeier, Crawford, & Tweed, 2003 ) are needed to tease apart the relative contributions of a strong prior of target not moving versus a strong expectation of greater intrinsic noise.…”
Section: Discussionmentioning
confidence: 99%